2018
DOI: 10.1039/c8ta00203g
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of nanostructured Pd/lanthanide-doped ceria spheres with high catalytic activity for CH4combustion

Abstract: Nanostructured 1 wt% Pd/LnDC spheres exhibited high activity for CH4 oxidation with total conversion of CH4 attained at a temperature below 400 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
2
10
1
Order By: Relevance
“…Indeed, in earlier papers it was already reported that Pd and ceria had a strong influence on the reciprocal redox behavior with palladium promoting low temperature CeO2 reduction and CeO2 promoting Pd oxidation [30,31], a situation confirmed also in more recent works [32][33][34]. The effect of ceria in the promotion of Pd oxidation, as suggested by Farrauto et al [18], has substantial implications for the high temperature methane oxidation activity of Pd-based catalysts and, if in the past this was mainly studied for energy production applications, at present it should be taken into account when considering for example close coupled three-way catalysts for methane abatement.…”
Section: Effect Of Ceria On Pdo Stabilization and Redox Behaviorsupporting
confidence: 57%
See 1 more Smart Citation
“…Indeed, in earlier papers it was already reported that Pd and ceria had a strong influence on the reciprocal redox behavior with palladium promoting low temperature CeO2 reduction and CeO2 promoting Pd oxidation [30,31], a situation confirmed also in more recent works [32][33][34]. The effect of ceria in the promotion of Pd oxidation, as suggested by Farrauto et al [18], has substantial implications for the high temperature methane oxidation activity of Pd-based catalysts and, if in the past this was mainly studied for energy production applications, at present it should be taken into account when considering for example close coupled three-way catalysts for methane abatement.…”
Section: Effect Of Ceria On Pdo Stabilization and Redox Behaviorsupporting
confidence: 57%
“…Other formulations involving close coupled Pd and ceria have been proposed in the literature, with Pd and ceria in separate domains interacting with each other [33,64,[96][97][98][99][100][101] or in which Pd is inserted into the lattice of ceria [17,20,22,40,43,46,54,102]. Regarding the first class of materials, it should be highlighted that in many cases from the characterization it is not clear whether they also might include Pd-Ce solid solutions, and the various catalyst configurations (nanosheets, nanospheres, Pd and ceria confined into porous supports etc.)…”
Section: Role Of Ceria On Catalytic Activitymentioning
confidence: 99%
“… 18 , 21 , 22 In particular, Pr can greatly improve the oxygen storage capacity of ceria because of its redox Pr 3+ /Pr 4+ couple. 21 , 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…18,21,22 In particular, Pr can greatly improve the oxygen storage capacity of ceria because of its redox Pr 3+ /Pr 4+ couple. 21,23,24 Though many reports are available on various methodologies, synthesizing enzymatic nanocrystals with controlled size and surface through a single method still remains a challenge. Yang nanorods (NRs) exposing different facets via a hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation